Wali Muhakkam for Muallaf in Muslim Minority Areas: A Juridical Analysis of the Determination of Itsbat Nikah by Religious Courts - Mirwan Mirwan; Firdaus Firdaus; Muchlis bahar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
An analysis of marriage validation (itsbat nikah) decisions by religious courts concerning the appointment of wali muhakkam for female converts (muallaf) in Muslim minority regions reveals that the process involves complex legal, social, and cultural considerations. These rulings not only focus on the formal legality of the marriage but also take into account the long-term implications for children born of the union and the alignment with the prevailing national legal system. This study aims to describe and analyze judges’ considerations regarding legal facts in the marriage of female converts using wali muhakkam, to explore the legal construction applied by judges in legitimizing the use of wali muhakkam, and to examine the arguments formulated by judges in validating such marriages. This research is categorized as a library study employing a normative juridical method with a statutory approach. Data sources are derived from established legal theories and documented judicial practices. The findings indicate that judges formulate legal arguments based on both Islamic legal principles and national law to validate the marriage of female converts conducted with a wali muhakkam. These rulings reflect the harmonization of religious values and state law, thereby ensuring justice, welfare, and legal certainty for all involved parties.